2012
DOI: 10.1002/app.37959
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photo‐polymerization of bio‐based furanic compounds functionalized by 2‐hydroxypropyl methacrylate group(s)

Abstract: Bio-based compounds (FmHPM and FdHPM) with a furan backbone and photo-polymerizable 2-hydroxypropyl methacrylate (HPM) group(s) were synthesized from carbohydrate-derived furanyl alcohols (furan-2-methanol and furan-2,5-dimethanol) and their photo-polymerizing behaviors and mechanical properties after photo-polymerization were investigated. Half time values (t 1/2 ) of bio-based FmHPM and FdHPM were 10.4 s and 3.0 s and their shrinkage ratios were 3.0 and 6.1% during photo-polymerization, respectively. Tensile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
(29 reference statements)
2
18
0
Order By: Relevance
“…Literature reports interesting studies on the replacement of MDGEBA prepolymer for VE networks. Thus, the use of isosorbide diglycidyl ether (Lukaszczyk et al, 2012;Sadler et al, 2013;Chrysanthos et al, 2011) or furfuryl derivatives (Jeong et al, 2013) was reported, but the properties of obtained materials do not meet the needed thermal properties for targeted applications. The synthesis of VE networks from vegetable oils is also reported in literature.…”
Section: From Acrylation Of Cardanol To Vinyl Esters Synthesismentioning
confidence: 99%
“…Literature reports interesting studies on the replacement of MDGEBA prepolymer for VE networks. Thus, the use of isosorbide diglycidyl ether (Lukaszczyk et al, 2012;Sadler et al, 2013;Chrysanthos et al, 2011) or furfuryl derivatives (Jeong et al, 2013) was reported, but the properties of obtained materials do not meet the needed thermal properties for targeted applications. The synthesis of VE networks from vegetable oils is also reported in literature.…”
Section: From Acrylation Of Cardanol To Vinyl Esters Synthesismentioning
confidence: 99%
“…Among the available literature on the synthesis of VE resins from renewable resources, few refer to aromatic monomers, and particularly cardanol. Indeed, some publications deal with prepolymers from glucose derivatives such as isosorbide , from wood derivatives such as furan , and extracted from plants such as phloroglucinol and vanillin . However, several publications concern acrylated vegetable oils used as reactive diluents of VE resins , or used as VE prepolymers .…”
Section: Introductionmentioning
confidence: 99%
“…The prepared assemblies were photo‐cured by irradiation using LED lamp. Based on a reported method, additional plates (2.54 × 5.08 cm 2 ) with the same thickness were attached on both ends of the specimens for grip. The tensile‐shear strengths of the joints bonded by the photo‐curing procedure were measured using universal testing machine (UTM) (5967, INSTRON, USA), and the loading rate was 1.27 cm/min.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, photo‐curable materials should be derived from petroleum‐independent and nontoxic chemicals instead of BPA. However, only a few examples of bio‐based photo‐curable materials bearing a rigid backbone have been reported …”
Section: Introductionmentioning
confidence: 99%